Motivasi Siswa dalam Pembelajaran Berbicara Menggunakan Permainan Bergambar Pada Siswa Kelas Tujuh di MTs Al-Munawaroh Cirebon - Noerjanah, Siti Luruh Ayu; Luthfiani, Trianis (Holistik: Journal for Islamic Social Sciences, 2019)
This research tried to find out the students motivation using picture games strategy in learning speaking of Mts Al-Munawaroh Kec. Pabedilan Kab. Cirebon. This research was based on the fact that the students still have problems during teaching learning English in the class, although they have been studying English every week. The research method uses qualitative method as known also by descriptive approach. The research finding as follows: 1) There are 28 from 30 (93.3%) students who states that picture games provide development and motivate the students in speaking skill can be seen from each activities that has been applied in the classroom. 2) Most the students states that picture game give motivating and make the students active in learning speaking. They have interesting activities. So they felt enthusiastic, excited, enjoy and active. 3) The effort from the teacher consists of four effort such as giving score, giving praise and reward, competition and punishment